1999
DOI: 10.1002/(sici)1096-9888(199912)34:12<1328::aid-jms889>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between antitumor drugs and a double-stranded oligonucleotide studied by electrospray ionization mass spectrometry

Abstract: Electrospray ionization mass spectrometry has been used to investigate the complex formation between a double-stranded oligonucleotide and various antitumor drugs belonging to two categories: intercalators (ethidium bromide, amsacrine and ascididemin) and minor groove binders (Hoechst 33258, netropsin, distamycin A, berenil and DAPI). The goal of this study is to determine whether the relative intensities in the mass spectra reflect the relative abundances of the species in the solution phase. The full scan MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
177
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 174 publications
(191 citation statements)
references
References 70 publications
13
177
1
Order By: Relevance
“…In the study by Gabelica, the DNA-binding modes observed in the gas-phase for ethidium bromide, amsacrine, and ascididemin exhibited the non-specific multiple-drug binding which parallels the binding behaviors observed in solution [16]. However, the relative peak intensities also paralleled ligand polarity, including ligand charge, and thus the observed binding pattern could simply be an artifact of the electrospray process.…”
Section: Complexation Of Dna and Uk-1 Analogs Without Metalsmentioning
confidence: 79%
See 3 more Smart Citations
“…In the study by Gabelica, the DNA-binding modes observed in the gas-phase for ethidium bromide, amsacrine, and ascididemin exhibited the non-specific multiple-drug binding which parallels the binding behaviors observed in solution [16]. However, the relative peak intensities also paralleled ligand polarity, including ligand charge, and thus the observed binding pattern could simply be an artifact of the electrospray process.…”
Section: Complexation Of Dna and Uk-1 Analogs Without Metalsmentioning
confidence: 79%
“…The lack of a well-defined DNA binding stoichiometry by the antibiotic analogs is reminiscent of results reported by Gabelica et al for drug-DNA complexes containing known intercalators such as ethidium bromide, amsacrine, and ascididemin [16]; as well as Kapur et al for the more complex intercalators daunomycin and nogalamycin [36]. In the study by Gabelica, the DNA-binding modes observed in the gas-phase for ethidium bromide, amsacrine, and ascididemin exhibited the non-specific multiple-drug binding which parallels the binding behaviors observed in solution [16].…”
Section: Complexation Of Dna and Uk-1 Analogs Without Metalsmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, distamycin binds in a 1:1 complex along AT-rich minor grooves of double-stranded (ds) DNA, but NMR studies suggest that it also binds in a head-to-tail fashion in a 2:1 complex with DNA [13]. Both of these stoichiometries have been observed in ESI-MS experiments [10,11,14].…”
mentioning
confidence: 99%